2020
DOI: 10.3389/fonc.2020.01747
|View full text |Cite
|
Sign up to set email alerts
|

Increased RAB31 Expression in Cancer-Associated Fibroblasts Promotes Colon Cancer Progression Through HGF-MET Signaling

Abstract: RAB family proteins participate in the dynamic regulation of cellular membrane compartments and are dysregulated in a variety of tumor types, which may alter the biological properties of cancer cells such as proliferation, migration, and invasion. In our previous study, we found that Ras-related protein Rab-31 (RAB31) expression was increased in late-stage colorectal cancer (CRC). The role of RAB31 has never been investigated in CRC. In this study, we found that expression of RAB31 in the tumor stroma but not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 61 publications
2
12
0
Order By: Relevance
“…To our knowledge, the findings that CCL20 induces secretion of HGF and phosphorylation of c-Met and that this pathway mediates the effects of CCL20 in eliciting migration and further secretion of CCL20 by colorectal cancer cells have not previously been reported in the literature. Our finding that signaling through the HGF/c-Met pathway induces migration of colorectal cancer cells is substantiated by several studies including those using the HT-29 and HCT116 cell lines [ 27 29 ]. In fact, the HGF/c-Met pathway has been implicated in the metastatic process of colorectal cancer [ 30 32 ].…”
Section: Discussionsupporting
confidence: 67%
“…To our knowledge, the findings that CCL20 induces secretion of HGF and phosphorylation of c-Met and that this pathway mediates the effects of CCL20 in eliciting migration and further secretion of CCL20 by colorectal cancer cells have not previously been reported in the literature. Our finding that signaling through the HGF/c-Met pathway induces migration of colorectal cancer cells is substantiated by several studies including those using the HT-29 and HCT116 cell lines [ 27 29 ]. In fact, the HGF/c-Met pathway has been implicated in the metastatic process of colorectal cancer [ 30 32 ].…”
Section: Discussionsupporting
confidence: 67%
“…Typically, the hepatocyte growth factor (HGF) can activate cancer cell invasion and metastasis. Consistently, it was reported that the migration of CRC cells could be promoted by the Ras-related protein Rab-31 (RAB31) through regulating HGF secretion in the tumor stroma (Yang et al, 2020). Human CRC-derived CAFs also enhance the adhesion of CRC cells to ECs by secretion of HGF (Zhang et al, 2019a).…”
Section: Epithelial-to-mesenchymal Transition Migration Invasion and Metastasismentioning
confidence: 73%
“…Hepatocyte growth factor (HGF), which is secreted predominantly by cancer-associated fibroblasts and present in the tumor microenvironment, promotes the survival and migration of cancer cells [26]. Rab31 was reported to promote the migration of colon cancer cell lines by paracrine HGF, and HGF inhibition abolished the migration of cancer cells mediated by Rab31 expression [27].…”
Section: Rab31 Promotes the Migration And Invasion Of Cervical Cancer Cells Via Mapk6mentioning
confidence: 99%